Hygienic Behavior of Adolescents in Choosing the Use and Disposal of Feminine Sanitary Napkins in Surakarta - Indarwati; Anjar Nurrohmah; Maryatun (Universitas Duta Bangsa Surakarta, 2026)
Introduction: Poor menstrual hygiene practices among adolescent girls, including incorrect sanitary pad usage and improper disposal, pose significant health concerns. Limited economic resources and inadequate sanitation facilities further lead some adolescents to use less hygienic alternative pads. The wide variety of sanitary pads available on the market also means adolescents may not prioritize pad quality. Objective: This study aims to describe adolescent girls' practices regarding sanitary pad usage, specifically concerning pad type selection, frequency of changing, handwashing practices, and pad disposal. Methods: This descriptive survey employed a quantitative approach, involving 101 adolescent girls who met the study criteria. Samples were purposively selected from several junior high schools in Surakarta. Results: Among the 101 adolescent girl respondents, 41% were 13 years old and in the 8th grade of junior high school. Regarding sanitary pad usage practices in Surakarta, 85.6% lived with their parents, and 78.2% chose disposable pads. Additionally, 52.5% changed their pads twice daily, 29.7% consistently washed their hands before and after using pads, 54.5% wrapped used pads before disposing them in the trash, and 45.5% rinsed pads with water to clean off blood before disposal. Conclusion: The majority of adolescents in this study primarily use disposable pads and change them twice daily (during morning and evening baths). However, not all adolescents wash their hands before and after using sanitary pads. Importantly, the practice of disposing of used pads is generally good, with most cleaning the pads, wrapping them in plastic, and then discarding them in the trash.